Biometric Registration of Migrants in the Process of Managing Migrant Crisis in Europe - Ivanović, Aleksandar R.; Ivanović, Aleksandar B. (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
In the paper, the authors deal with the issue of how systems for biometric identification are being used to manage the migrant crisis in Europe. Regarding that, the authors' underlying problem of identification of migrants, due to the fact that many migrants escaping from the war don’t always have a personal identification document with them, which means a lot of problems from state authorities in the countries where they are seeking asylum. With the intention to provide balance between need to quickly process, protect and place huge numbers of refugees, on one side, and maintaining security, on the other side, authors try to represent the importance of implementing biometrics identifications system of migrants as well as cooperation and sharing of that data’s between neighbour countries which are on the so called migrants routes to Europe.